Numerical assessment of the loading of rolling contact fatigue cracks close to rail surface irregularities. Issue 5 (11th December 2019) - Andersson, Robin; Kabo, Elena; Ekberg, Anders
Abstract: Rolling contact fatigue damage of railway rails in the form of squats, characterised by local depressions and cracks located at the rail surface, has been linked to the occurrence of local rail surface irregularities. This study concerns rolling contact fatigue cracks in the vicinity of fairly smooth surface irregularities, here denoted dimples. The influence of factors such as dimple geometry, cluster effects, and crack size is evaluated. To this end, dynamic vehicle–track simulations featuring realistic wheel and rail profiles are employed to characterise the dynamic impact during a wheel passage. The contact load in the vicinity of the dimples is then mapped onto a 3D finite element model of a rail section containing a crack in the rail head. The crack loading is finally quantified by multimodal stress intensity factors. The analyses establish that also shallow dimples might have a significant impact on the crack loading. This effect is increased for larger or multiple irregularities but decreases as the crack grows.